MEDIA-BASED LEARNING: A THEORETICAL METASTUDY - Giessen, Hans (European Scientific Journal, ESJ, 2014)
Media-based learning does not necessarily make sense nor is it necessarily effective, for that matter, simply because it uses a medium. Rather, there are several variables that can and do influence its success: the very medium, the content, and the learner’s cognitive styles. For example, it is necessary to accept the difference between native language learning, second language acquisition, plurilingualism, language learning programs for children or adult learners, for visual or auditive or kinesthetic types ... Of course, all these variables and more have to be taken into consideration, alone and interacting, in order to decide whether and where media-based learning is to be used, and where it might be counterproductive.